2004
DOI: 10.1158/1078-0432.ccr-04-0477
|View full text |Cite|
|
Sign up to set email alerts
|

High Levels of Phosphorylated Form of Akt-1 in Prostate Cancer and Non-Neoplastic Prostate Tissues Are Strong Predictors of Biochemical Recurrence

Abstract: Akt is a serine-threonine-kinase that phosphorylates proteins in several pathways regulating aspects of metabolism, apoptosis, and proliferation. Akt signaling promotes proliferation and increased cell survival and is thought to play an important role in prostate cancer progression. Tissue microarrays (640 patients) with triplicate cores of nonneoplastic prostate, BPH, and index tumor were immunostained with antibody to Phospho-Akt (Ser473), digitized, and quantified. The expression index (Intensity*Percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
3
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(197 citation statements)
references
References 10 publications
12
177
3
5
Order By: Relevance
“…Work using human prostate tissue confirms that pAkt 473 is expressed in PIN and invasive prostate cancer, and staining intensity positively correlated with PSA levels and Gleason grades (Ghosh et al, 2003;Altomare and Testa, 2005;Majumder and Sellers, 2005). In addition, a large study of 640 radical prostatectomy specimens demonstrated that high levels of pAkt was predictive of biochemical recurrence (Ayala et al, 2003). Although in our current cohort we did not observe a significant association with pAkt 473 and biochemical recurrence (pAkt 473 ; P ¼ 0.151, results not shown), the Kaplan -Meier curves did separate and the difference in the median time to biochemical recurrence in the two groups was 1.8 year compared to 2.4 years, suggesting that significance might have been meet if a larger cohort had been used.…”
Section: Protein Expression Patternsmentioning
confidence: 85%
See 1 more Smart Citation
“…Work using human prostate tissue confirms that pAkt 473 is expressed in PIN and invasive prostate cancer, and staining intensity positively correlated with PSA levels and Gleason grades (Ghosh et al, 2003;Altomare and Testa, 2005;Majumder and Sellers, 2005). In addition, a large study of 640 radical prostatectomy specimens demonstrated that high levels of pAkt was predictive of biochemical recurrence (Ayala et al, 2003). Although in our current cohort we did not observe a significant association with pAkt 473 and biochemical recurrence (pAkt 473 ; P ¼ 0.151, results not shown), the Kaplan -Meier curves did separate and the difference in the median time to biochemical recurrence in the two groups was 1.8 year compared to 2.4 years, suggesting that significance might have been meet if a larger cohort had been used.…”
Section: Protein Expression Patternsmentioning
confidence: 85%
“…Prostate tumours are reported to have significantly higher Akt expression than BPH (Liao et al, 2003), and only 10% of well-differentiated prostate tumours strongly express pAkt compared to 92% of poorly differentiated tumours (Malik et al, 2002;Ayala et al, 2003;Ghosh et al, 2003). Akt1 and Akt2 expression in hormone-sensitive tumours have been associated with shorter time to biochemical relapse; however, no association was reported with the activated forms or with survival (Le Page et al, 2006).…”
mentioning
confidence: 99%
“…Preoperative prostate-specific antigen (pre-PSA) level ranged from 0.3 to 97.5 ng/mL (mean, 10.36 ng/mL), with 30% of patients having a pre-PSA level greater than 10.36 ng/mL. Lower Gleason score (GS) (3)(4)(5)(6) was present in 33% patients, whereas 67% had a higher GS (7)(8)(9)(10). Biochemical recurrence occurred in 15.5% of patients, whereas 5.6% had lymph node (LN) metastases.…”
Section: Clinical and Pathologic Characteristicsmentioning
confidence: 99%
“…This could explain why PCa can respond to initial androgen withdrawal, but many patients with PCa end up with recurrence and androgen independence, leading to accelerated disease progression and death [2,3]. A number of regulatory pathways such as androgen receptor (AR) signaling pathway [4,5], mitogen-activated protein kinase signaling pathway [6], and Akt/PKB (protein kinase B) signaling pathway [7,8] may play critical roles in prosurvival/proliferation in PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Using tissue microarray technology in a large cohort of patients, we have identified that a high level of P-Akt in prostate cancer was predictive of a higher probability of recurrence on univariate and multivariate analysis with hazard ratios considered high on semiquantitative analysis. 117 Since most patients fall within the Gleason 6 and 7 categories, and because of the known limitations of Gleason scoring, we tested P-Akt for its predictive capacity within the subgroup. We found that P-Akt level is also an independent prognostic indicator of survival when Gleason 6 and 7 patients were analyzed separately.…”
Section: Molecular Biomarkers Based On Akt Activitiesmentioning
confidence: 99%